How to improve the quality of care of obese patients with type 2 diabetes mellitus receiving care at a semirural district hospital in Lesotho - Nkulu, Patrick Mulongo (Stellenbosch : Stellenbosch University, 2019)
Thesis (MFamMed)--Stellenbosch University, 2019.